# Unable To Understand The Difference Between $(-3)^4$ And $-3^4$

Why is $(-3)^4 =81$ and $-3^4 =-81$?This might be the most stupidest question that you might have encountered,but unfortunately i'am unable to understand this.

-

By definition

$(-3)^4 = (-3)\cdot(-3)\cdot(-3)\cdot(-3) = 9\cdot 9 = 81$

$-3^4 = -(3^4) = -(3\cdot 3\cdot 3\cdot 3) = - 81$

-

Note that $(-3)^4=((-1)\cdot3)^4=(-1)^4\cdot3^4=81$

Again note that $-3^4=(-1)\cdot3^4=-81$

-
and then we understand the difference between $(-1)^4$ and $-1^4$. – Parth Kohli Jan 24 '13 at 10:12
@Novice: I think OP need to understand this fact that you are given. – A.D Jan 24 '13 at 10:13

$$(-3)^4 = -3 \cdot -3\cdot -3\cdot -3 = 9\cdot9=81$$Now, when we have to "simplify" the expression $-3^4$, first we do the exponent and then the rest. So this simplifies to $-(81) = -81$

This question had confused me a lot too, and then I got my enlightenment (now waiting for the badge)...

-
Good Refresher Isn't it! +1 for you too! – alok Jan 24 '13 at 10:24

Because multiplication doesn't distribute into exponentiation. That is, $a(b^c) = (ab)^c$ doesn't always hold. And there's no reason why it should, unless $c = 1$. So $(-3)^4 = (-1 \cdot3)^4 = (-1)^4 \cdot (3)^4 = 81$, and not $-81$, as the multiple of $-1$ doesn't factor out.

-